1992
DOI: 10.1038/ng1192-240
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal glands are the predominant site of CFTR expression in the human bronchus

Abstract: We have used in situ hybridization and immunocytochemistry to characterize the cellular distribution of cystic fibrosis (CF) gene expression in human bronchus. The cystic fibrosis transmembrane conductance regular (CFTR) was primarily localized to cells of submucosal glands in bronchial tissues from non-CF individuals notably in the serous component of the secretory tubules as well as a subpopulation of cells in ducts. Normal distribution of CFTR mRNA was found in CF tissues while expression of CFTR protein wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
393
7
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 613 publications
(424 citation statements)
references
References 39 publications
22
393
7
2
Order By: Relevance
“…Furthermore, CFTR regulates sodium transport across epithelial membranes through interactions with the epithelial sodium channel ENaC [9], and facilitates the trans-membrane export of the small organic anionic peptide glutathione [10]. The expression of CFTR is located in the apical membrane of epithelial cells that line mucous membranes and submucosal glands [11,12]. The tissues most affected by CFTR deficiency include the vas deferens, exocrine pancreas, liver, large intestine, sinuses, and the lower airways.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CFTR regulates sodium transport across epithelial membranes through interactions with the epithelial sodium channel ENaC [9], and facilitates the trans-membrane export of the small organic anionic peptide glutathione [10]. The expression of CFTR is located in the apical membrane of epithelial cells that line mucous membranes and submucosal glands [11,12]. The tissues most affected by CFTR deficiency include the vas deferens, exocrine pancreas, liver, large intestine, sinuses, and the lower airways.…”
Section: Introductionmentioning
confidence: 99%
“…Submucosal glands are well developed in human airways and comprise a system of mucous (mucin-secreting) and serous (fluid-secreting) acinar tubules and conducting ducts that secrete a mixture of mucins and liquid into the lumen of large airways (Burkitt et al, 1996). An important study (Engelhardt et al, 1992) reported that CFTR expression in human lungs was highest in submucosal gland acini, suggesting that decreased gland output of fluid and antimicrobial factors might cause CF lung disease (Jiang and Engelhardt, 1998). However, compelling physiological evidence has recently accumulated suggesting that the superficial epithelium controls the volume of liquid on airway surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relative contribution of the superficial epithelium and submucosal glands to ASL volume homeostasis and thus to CF airway pathogenesis remains controversial (Verkman et al, 2003). Historically, submucosal glands, not the superficial epithelia, have been considered as the main site of CFTR expression in the lungs (Engelhardt et al, 1992). Submucosal glands are well developed in human airways and comprise a system of mucous (mucin-secreting) and serous (fluid-secreting) acinar tubules and conducting ducts that secrete a mixture of mucins and liquid into the lumen of large airways (Burkitt et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Using various glycosylated polylysines as vectors, we have shown that some sugars enhanced the vector capability of polylysine and yielded high expression of the reporter gene lucifer- …”
Section: Figure 2 Gene Transfer With Nonviral Vectors Into Immortalizmentioning
confidence: 99%